(untitled) (Journal of the Management Sciences, 2024)
The unending controversies surrounding the issues of democratic governance and electoral processes in Nigeria has continued to receive increased attention of scholars of diverse backgrounds because of the crucial role it plays in any organized political system. The broad objective of this paper is to determine the effect of electoral violence on Nigeria’s democracy, with particular reference to the 2023 general elections. The study was also guided by three specific goals and three research questions. Data for this study were gathered from both primary and secondary sources. The study anchored on the theory of ‘Social Contract’ as a framework for analysis. Findings of the study revealed that the 2023 general elections in Nigeria were grossly characterized by unabated malpractices and deliberate attempts by the ruling All Progressive Congress (APC) to further consolidate state power, against the wish of majority of the country’s population. It also discovered that the verdict of the Presidential Electoral Petitions Tribunal further dampened the hope of citizens, thus, deepening the already existing attitude of political apathy which is detrimental to the growth of democracy in the country. The study concludes that the 2023 general elections have been adjudged by political and social affairs analysts as the worst election in Nigeria, since the return to the so-called democracy in 1999. It recommends, above all, that Nigerians should advocate for ideal democracy which guarantees a clearcut separation of power among the various arms of government to ensure checks and balances, and that there is urgent need to embrace electronic voting and electronic transmission of results as a panacea to vote-buying in the country.